Analisis Kesesuaian Pemanfaatan Ruang Tahun 2015 Terhadap Rencana Detil Tata Ruang Kota (RDTRK) Kecamatan Klaten Selatan Tahun 2013-2018 - Setyaningtyas, Betania Putri Angga Sari, Drs. Priyono, M.Si (2017)
South Subdistrict Klaten Klaten district is an area of study in this research. The purpose of this study was to analyze the suitability of the actual space utilization of the Detailed Spatial Plan of the City District South Klaten and analyzes the factors that influence the suitability of species variation utilization of space in the District of South Klaten. The method used in the research is to overlay and indirect observation. Analytical methods of Determining the suitability of the use of space and space utilization suitability factor changes made by a qualitative method using overlay analysis with the help of Geographical Information Systems (GIS). Field checks Carried out to match the results of space utilization of data interpretation Worldview existing image with the real situation in the field along with a documentation form the utilization of space in the field, so it can be used to test the accuracy / precision of interpretation, as well as to limit the actual space utilization and its Amendments. Results from this study is the development of the Southern District of Klaten in 2015, in general, the conversion of agricultural land into non-agricultural, Appropriate criteria dominate South Klaten District of Conformity utilization level criteria for the villages of the Reviews largest in the village Glodogan amounted to 99 969% of the area of the village of Glodogan. The criteria do not fit are second at 135 745 ha, or 8,891% and occurred in the village of Trunuh that is equal to 2,716% of the area of the village of Trunuh. The criteria have not been suitable for 6,040 hectares or 0395% and occurred in the village of Danguran that is equal to 1.270% of the area of the village of Danguran. Factors that Affect the utilization of space in the District of South Klaten is public awareness of the regulations, population growth, business interests, with the establishment of social adequate facilities and their accessibility